Building Self-Confidence Amidst Trauma: A Study of Adolescents with Adverse Childhood Experiences - Firmansah, Fais; Widiantoro, FX Wahyu (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Adolescents with adverse childhood experiences (ACE) are at higher risk of developing psychological problems, including social anxiety. Social anxiety may hinder adolescents’ social and emotional development, while self-confidence is considered a protective factor that reduces the negative impact of ACE. This study aims to examine the relationship between self-confidence and social anxiety among adolescents with ACE in Kulonprogo. A quantitative method was employed with self-confidence as the independent variable and social anxiety as the dependent variable. This study employed a quantitative method with self-confidence as the independent variable and social anxiety as the dependent variable. The research instruments consisted of a self-confidence scale (α = 0.87) and the Social Anxiety Scale for Adolescents (SAS-A) (α = 0.91), both of which have been adapted into Indonesian. Participants were adolescents aged 18–23 years who experienced ACE and resided in Kulonprogo. The results indicated a significant negative relationship between self-confidence and social anxiety. Higher levels of self-confidence were associated with lower social anxiety, and vice versa. The strength of the relationship was in the moderate category (r=-0,42). Furthermore, most participants demonstrated high levels of social anxiety (61%) and moderate levels of self-confidence (84%). These findings highlight the crucial role of self-confidence in mitigating social anxiety among adolescents with ACE and may serve as a reference for developing more targeted psychological interventions. Remaja dengan pengalaman buruk masa kanak-kanak atau adverse childhood experience (ACE) berisiko lebih tinggi mengalami gangguan psikologis, termasuk kecemasan sosial. Kecemasan sosial dapat menghambat perkembangan sosial dan emosional remaja, sementara kepercayaan diri dipandang sebagai faktor pelindung yang mampu menurunkan dampak negatif ACE. Penelitian ini bertujuan untuk mengetahui hubungan antara kepercayaan diri dengan kecemasan sosial pada remaja yang mengalami ACE di Kulonprogo. Penelitian menggunakan metode kuantitatif dengan variabel kepercayaan diri sebagai variabel bebas dan kecemasan sosial sebagai variabel terikat. Sampel pada penelitian ini berjumlah 100 remaja berusia 18-23 tahun yang dipilih melalui metode non-probability sampling dengan teknik quota sampling. Pengumpulan data dilakukan menggunakan skala likert yang menggunakan sistem dua arah pernyataan yaitu favorable dan unfavorable. Penelitian ini dianalisis menggunakan korelasi product moment pearson dengan menggunakan perangkat lunak SPSS versi 20.00. Hasil analisis menunjukkan adanya hubungan negatif yang signifikan antara kepercayaan diri dengan kecemasan sosial. Semakin tinggi kepercayaan diri, maka semakin rendah kecemasan sosial, demikian pula sebaliknya. Temuan ini menegaskan pentingnya peran kepercayaan diri dalam mengurangi kecemasan sosial pada remaja dengan ACE serta dapat menjadi dasar bagi intervensi psikologis yang lebih tepat sasaran.